New cave species of Sinella Brook, 1882 from China (Collembola: Entomobryidae) - Zhao, Lina; Zhang, Feng (Zootaxa, 2016)
Springtails, especially entomobryids, are abundant in Karst faunas. Five new species of Sinella Brook are described here from caves in southern China: S. liuae sp. nov., S. hunanica sp. nov., S. tigris sp. nov., S. minuta sp. nov. and S. tiani sp. nov. A new record of Sinella sineocula Chen & Christiansen, is also recorded. These species differ in claw structure, chaetae on ventral side of the head, and body chaetotaxy. An updated key to cave species of Sinella from China is provided.